Membrane structures in the Tropics: building technology and climate adaptation - Flor, Jan-Frederik (2019)
Adaptation to climate has played an essential role in the history of architectural design and is becoming even more important in times of climate change. However, contemporary buildings and structures, as in the case of tensioned membrane structures, often lack the cycling process of adaptation that traditional constructions have undergone over time. The objective of the study presented in this paper is to investigate the principles and strategies that enhance the climatic performance of tensioned membrane structures in the Tropics. The study focusses on the proposal of specific design strategies for the early design stage ofmembrane projects. The strategies are based on passive and bioclimatic principles to create thermal comfort conditions without additional energy input. In the first part of this article, an overview of the development and use of membrane structures in the tropical regions is outlined, highlighting formal and functional requirements of geometry and material. In the second part, the climatic elements which are relevant to thermal comfort in the Tropics are addressed with specific design strategies and synthesized by schematic diagrams and drawings, showing different design solutions for geometries and details of typicalmembrane structures. In the third part, three case studies are presented, exemplifying the analytic processes and implemented design strategies in a real case scenario. The study concludes with passive design guidelines applied to membrane structures and argues for a climate-adaptive design approach of light-weight architecture in tropical regions.